Social Capital and Civil Society - Fukuyama, Francis (Washington, D.C. : International Monetary Fund, 2000)
Social capital is an instantiated informal norm that promotes cooperation between individuals. In the economic sphere it reduces transaction costs, and in the political sphere it promotes the kind of associational life that is necessary for the success of limited government and modern democracy. Although social capital often arises from iterated Prisoner's Dilemma games, it also is a byproduct of religion, tradition, shared historical experience, and other types of cultural norms. Thus whereas awareness of social capital is often critical for understanding development, it is difficult to generate through public policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet